Hydrodynamic Load Benchmarking on Bottom-Seated Cylinders in Finite Depths: A Frequency-Domain Comparison of Analytical and Open-Source BEM Solutions - Sarantidis, Sarantos; Mazarakos, Thomas P. (Technical Annals, 2024)
The scope of the presented paper is a benchmark study between the results of analytical and Boundary Element Method (BEM) solutions for the hydrodynamic problem of a vertical fixed cylinder due to the action of linear waves. First-order hydrodynamic exciting wave forces and moments, added mass, hydrodynamic damping coefficients, and the Response Amplitude Operators (RAOs) for the surge motion are calculated. The mean second-order wave drift forces are also given by using the direct integration method. The analytical solution is calculated in the frequency domain for a wide range of frequencies for different cylinder characteristics. Finite water depths and linear waves are considered. Therefore, a formulation of the problem based on the Laplace equation and boundary conditions on the free surface and seabed, is given. Also, two different open-source BEM codes are used to solve the hydrodynamic problem. The calculated results are compared to those of other investigators’ analytical and numerical predications.